Helat-related quality of life from the perspective of adolescent students (Research, Society and Development, 2023)
Introduction: Adolescence is defined by the World Health Organization (WHO) as the period between 10 and 19 years of age, marked by biological, physiological and psychosocial changes. Health-related quality of life (HRQoL) is understood as a multidimensional construction of the components of physical, emotional, mental, social, cultural and behavioral well-being from the adolescent's perspective. Objective: To identify health- related quality of life from the perspective of adolescents from the 6th to the 9th grade of elementary school II. Methodology: A quantitative approach study with adolescents from the 6th to the 9th grade of elementary school in a public school in the city of Divinópolis/MG. For data collection, the Kidscreen-27 questionnaire was used, children version. Results and discussion: Sixty adolescents participated in the study. The results showed that quality of life is a multidimensional construct that allows adolescents to form and consolidate fundamental concepts for their identity and health. Final considerations: Kidscreen-27 is a tool that enables an assertive approach to the psychosocial aspects that permeate adolescence, and through which it is possible to identify the context of adolescents and their perspectives on health.